Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.4209/aaqr.2016.04.0144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Butanol Blends on Nano Particle Emissions from a Stationary Conventional Diesel Engine

Abstract: In this study, combustion characteristics and nano-size soot particle emissions from a stationary conventional diesel engine have been experimentally investigated using butanol/diesel blends. Experiments were conducted on a single cylinder stationary diesel engine at a constant speed of 1500 rpm for neat diesel and butanol/diesel blends (i.e., 10%, 20% and 30% butanol on volume basis) at different engine loads. Piezoelectric pressure transducer installed in the engine combustion chamber was used for measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Yang et al (2007) also reported that total PAH concentrations and their BaP eq emissions could be reduced by using B20, when HC, CO, PM, and particulate phase PAH emissions increased with accumulated mileage. The higher viscosity could be the reason that led to several durability issues, such as deposition formation, carbonization of injector tip, fuel filter plugging (Saxena and Maurya, 2016) and cause the increasing emissions.…”
Section: Durability Test and Deterioration Of Diesel Enginementioning
confidence: 99%
“…Yang et al (2007) also reported that total PAH concentrations and their BaP eq emissions could be reduced by using B20, when HC, CO, PM, and particulate phase PAH emissions increased with accumulated mileage. The higher viscosity could be the reason that led to several durability issues, such as deposition formation, carbonization of injector tip, fuel filter plugging (Saxena and Maurya, 2016) and cause the increasing emissions.…”
Section: Durability Test and Deterioration Of Diesel Enginementioning
confidence: 99%
“…Diesel engines are major source of emissions including particulate matter (PM), nitrogen oxides, sulfur oxides, total hydrocarbons, carbon dioxide, carbon monoxide as well as toxic chemicals such as polycyclic aromatic hydrocarbons Tsai et al, 2015). However, it is well known that PM emissions from diesel engines are are relatively high, due to the combustion of heterogeneous mixture in the cylinder at higher combustion temperatures (Saxena and Maurya, 2016). PM, also known as soot, is primarily composed of carbon but also includes some other organic and inorganic compounds (ash), some sulfur compounds and some metal traces from unburnt fuel and lubricating oil (Li, 2011;Sharma et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Biodiesel can reduce some of the pollutants like PM, CO, HC and POPs, because of its higher oxygen content, it results in a more complete combustion (Raheman and Ghadge, 2007;Lin et al, 2010;Yu et al, 2014). On the other hand, the cost of production, higher viscosity and lower heating value are the main shortcomings of using biodiesel in the diesel engine (Saxena and Maurya, 2016).…”
Section: Introductionmentioning
confidence: 99%